Abdul Halim Majalengka dan Pengembangan Pendidikan Islam dalam Persyarikatan Ulama - Alfiana Sari; Imroatun Nur'aini; Mayra Aninda Nur Syifa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines KH. Abdul Halim from Majalengka, a figure who had a unique approach to advancing Islamic education during the colonial period. The main focus of this study is to answer how he was able to transform the mentality of society at that time, which tended to be passive, underdeveloped, and left behind in various aspects of life. This research uses a historical research method with a document analysis approach to explore the ideas and educational practices he implemented. The findings show that the key to KH. Abdul Halim’s success lies in the concept of “Independence” (Self-Help), which emphasizes the importance of the ability to stand on one’s own without relying on others. He then established an educational institution called Santri Asromo, which integrated religious learning with practical skills such as farming, trading, and carpentry. Through this system, the students were not only equipped with the ability to read the Qur’an and understand religious teachings but also with life skills that enabled them to be economically independent. In conclusion, KH. Abdul Halim’s thinking proves that ideal Islamic education must be able to combine faith values with practical skills. The findings of this study serve as an important reminder for today’s educational institutions that quality education is one that can produce independent, moral individuals who are ready to face real-life challenges.